The Responsibility of Tasawuf to the Millenial Generation - Ahmad Idhofi (UIN Sunan Gunung Djati Bandung, 2021)
Seeing modern life with various achievements in many fields, which are characterized by a luxurious lifestyle, should be able to lead people to a calm and happy life, but the reality shows otherwise that worldly achievements alone are not able to deliver humans to the desired condition. This fact indicates that there is another element of human beings that demands to be fulfilled, namely the spiritual element. This research will explore how is the responsibility of Sufism in the millennial generation? This research belongs to the literature review and uses analytical and deductive methods. Through this paper, it is found that the values contained in Sufism will be able to train the soul and mentality of the millennial generation so that they can live in balance in the midst of materialist and hedonic worldly influences in obedience to the creator. Humans who have entered into spiritual life will find and practice the values of Sufism in their lives in the form of wara '(tawadu'), simple, ta'abbud (devoted), and zuhud, (not bound by luxury).